Efficiency and Risk Analysis of Hospital Supply Chain and Strategy Development Using FMEA and Swot: A Case Study of Husada Hospital - Julianto; Saparso; Gunardi, Wani Devita (Journal Research of Social Science, Economics, and Management, 2026)
Efficient supply chain management (SCM) is essential for ensuring service continuity, cost efficiency, and patient safety in hospitals. This study aims to analyze the efficiency of the hospital supply chain, identify critical operational risks, and formulate strategic recommendations for improving logistics performance at Husada Hospital, Jakarta. A mixed-methods approach was employed by integrating quantitative inventory analysis with qualitative risk and strategic analyses. Quantitative assessment included demand patterns, lead time, inventory coverage, and inventory control indicators, while qualitative analysis involved process mapping, in-depth interviews, Failure Mode and Effects Analysis (FMEA), Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal–External (IE) Matrix, and SWOT analysis. The findings reveal that the existing supply chain is supported by a structured procurement and distribution workflow but remains highly dependent on manual planning, periodic reviews, and experiential decision-making. FMEA identified inventory planning, critical-item management, and supplier coordination as the highest-priority risk areas. The IFE score of 2.481 and EFE score of 2.427 positioned the organization within Cell V of the IE Matrix, indicating a hold-and-maintain strategic posture. Consequently, the recommended strategy emphasizes strengthening data-driven inventory planning, optimizing information systems, standardizing inventory parameters, improving vendor mapping and performance monitoring, establishing risk registries, and implementing risk-based approval mechanisms. These findings contribute to hospital supply chain management by demonstrating that sustainable logistics performance is achieved not through extensive structural changes but through systematic enhancement of planning accuracy, inventory control, risk mitigation, and strategic decision-making, thereby supporting operational resilience and improving healthcare service quality.